2014
DOI: 10.1515/pac-2013-1022
|View full text |Cite
|
Sign up to set email alerts
|

Use of Raman spectroscopy for continuous monitoring and control of lignocellulosic biorefinery processes

Abstract: The production of fuels and chemicals from lignocellulosic biomass demands efficient processes to compete with fossil fuel-derived products. Key biorefinery processes, such as enzymatic hydrolysis of cellulose and microbial fermentation, can be monitored by advanced sensors in real time, providing information about reactant and product concentration, contamination, and reaction progress. Spectroscopic techniques such as Raman spectroscopy provide a means of quickly and accurately assessing many types of reacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…However, the Raman signal is relatively weak and attenuated mainly by the suspended solid particles and by the background fluorescence emitted by lignin [48], altogether, limiting its potential for in-line monitoring. Ewanick et al [49,50] UV-Vis spectroscopy is often not considered as a method for real-time monitoring of fermentations because it cannot detect many key compounds (e.g. glucose or ethanol) and because the light scattering caused by the suspended solid particles dominates the absorption process [35,52].…”
Section: Vibrational Spectroscopymentioning
confidence: 99%
“…However, the Raman signal is relatively weak and attenuated mainly by the suspended solid particles and by the background fluorescence emitted by lignin [48], altogether, limiting its potential for in-line monitoring. Ewanick et al [49,50] UV-Vis spectroscopy is often not considered as a method for real-time monitoring of fermentations because it cannot detect many key compounds (e.g. glucose or ethanol) and because the light scattering caused by the suspended solid particles dominates the absorption process [35,52].…”
Section: Vibrational Spectroscopymentioning
confidence: 99%
“…Raman and infrared spectroscopies have been extensively used separately as phenotyping tools in a wide range of microbial metabolomics investigations including studying the effects of antibiotics in bacteria [ 11 , 12 ], classifying and identifying microbial species and strains [ 2 , 3 , 13 ], effects of environmental factors on microbial growth [ 14 , 15 ], and microbial-derived products such as beverages [ 16 , 17 ], biofuels [ 18 , 19 ] and other products for human and animal health. Both methods are often used together in the same study in a complementary way as each technique may be advantageous when studying certain types of samples or biological processes as a result of their different basic working principles [ 3 , 14 , 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…In other words, I ( v ) R ∝ N . Several research groups have demonstrated the potential of using Raman spectroscopy and univariate calibration with a calibration curve for real-time monitoring of lignocellulosic bioethanol production, including pretreatment, hydrolysis, and fermentation steps. However, the complexity of biomass and biomass-derived samples often limits the utility of univariate calibration with these types of samples. Another direction for quantitative analysis is to use Raman spectra along with data from another analysis method (such as HPLC) to build regression models.…”
Section: Introductionmentioning
confidence: 99%